Mobility and feeding strategies in the pastoral systems of the Syrian Badiah - Dutilly-Diane C.; Saint-Macary C.; Tiedeman J.; Arab G.; Batikha N.; Ghassali F.; Khoudary E. (Mediterranean livestock production: uncertainties and opportunities, 2008)
The pastoral system of Syria, like most of West Asia and North Africa, is under stress with growing sheep population and continuous degradation of the rangelands. While the research and development society is strongly promoting community rangeland management in a participative and collaborative way, it is essential to characterize and assess the level of dependence the Bedouins are having today with regard to their community rangelands. Using information related to animal mobility and feeding patterns of 313 Bedouin households and their respective community characteristics, we identified 5 strategy types and in a second step explained the probability for a household to adopt one strategy over another. Results show the strong role of community characteristics in determining those choices and in particular the relationship with the cropping zone.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)